PENERAPAN PENDEKATAN SAINTIFIK UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV SD NEGERI 45 PEKANBARU - Feni Vanelia Vanelia; Mahmud Alpusari Alpusari; Otang Kurnia Kurnia (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research to improve the learning outcomes grade IV of SD Negeri 45 Pekanbaru through a scientific approach. Implementation of research in November 2014. The subjects were students grade IV of SD Negeri 45 Pekanbaru with 35 students. Minimum completeness criteria of SD Negeri 45 Pekanbaru is 75. Based on the first score, students who campleted is a 14 students ( 40 % ) and students who do not completed is a 21 students ( 60 % ) of the 35 students consisting of 18 female’s and 17 male’s. With an average of 71,00. The learning outcomes increase 5,83% for the first daily test with an average is 75,14 and 13,04% in daily test II with an average is 80,26. Researcher served observation sheets to observe the activities of teacher and student. The percentage of teachers activity in cycle I meeting I was 50 % and the meeting II is 60 %, in cycle II meeting I was 70 % and the meeting II is 80 % and percentage of students activity in cycle II meeting I was 50 % and the meeting II is 70 %, in cycle II meeting I was 75 % and meeting II is 95 %. The conclusion of research is the aplication of scientific approaches to improve learning outcomes of grade IV of SD Negeri 45 Pekanbaru in academic year of 2014/2015. Keyword : Scientific Approach, Students Learning Outcomes